EP1303 Creation of an Y-shaped ileal neobladder in 10 logical steps. (1st November 2019) - Martínez Gómez, C; Angeles, MA; Del, M; Malavaud, B; Martinez, A; Ferron, G
Abstract : Introduction/Background: Anterior pelvic exenteration is a salvage procedure carried out in patients with recurrent or persistent gynecological malignancies involving the bladder. The type of urinary reconstruction is chosen according to the patient preferences after preoperative counselling. Bricker´s ileal conduit is a non-continent urinary diversion, and it is the most frequently employed among gynecological oncologists. However, continent diversions seem to improve patient´s quality of life in patients. Unfortunately, these techniques are not well-known among surgeons and have a low acceptance. In this video, we aimed to describe and standardize orthotopical ileal neobladder creation. Methodology: This video shows the creation of an orthotopical Y-shaped neobladder in ten consecutive steps. The surgery was performed on a 34-year-old woman treated by extended chemoradiotherapy for a stage IIIC2 cervical cancer. At the end of the treatment, a symptomatic vesicovaginal fistula was evidenced at physical examination and at magnetic resonance imaging. In this situation, a closure surgery was proposed to the patient. Taking into consideration that the urethra and the neck of the bladder were competent and not involved by the tumor or the fistula, an orthotopical ileal neobladder was performed following patient's choice. Results: This video displays the creation of a Y-shaped orthotopic ileal neobladder in the 10 following steps: 1: Patient selection 2: Omental j-flap 3: Selection of the ileal loop 4: Stapled side-to-side ileoileal anastomosis 5: Y-shaped detubularization of the ileal loop 6: Ureter spatulation and ureteral stents insertion 7: Ileoureteral anastomosis 8: Posterior Ileovesical anastomosis 9: Anterior Ileovesical anastomosis 10: Blue dye testing Conclusion: Orthotopic ileal neobladder reconstruction may be an option after anterior pelvic exenteration in selected patients fulfilling a restrictive selection criteria. As previously published, standardization of surgical procedures in 10 steps enhances learning of complexes techniques. Disclosure: Nothing to disclose